PENGARUH KONSENTRASI KITOSAN TERHADAP PROSES FLOKULASI PADA PEMANENAN MIKROALGA - Rangga Warsita Aji; Wulan Sari Gusniawati; Nur Rokhati (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
The common method used for harvesting microalgae is filtration. But, it has disadvantages such as particle size of microalgae are generally small causing the harvesting process uneffecient. It can be measure using chitosan as bioflocculant. The first procedure of research is making a stock solution of chitosan was prepared by dissolving chitosan flakes in 1% (v/v) acetic acid until the flakes was totally dissolved, then  it is introduced  into 500 ml of microalgae culture (Spirulina sp). The flocculation process is experimental designed by the variation of the concentration of chitosan (5 mg/L ; 10 mg/L ; 15 mg/L ; 40 mg/L ; 70 mg/L ; 100 mg/L) at pH 8 and slow mixing speed 40 rpm.  The result shows that increasing concentration of chitosan causes increasing flocculation efficiency but at the concentration that is too high, it will make flocculation efficiency decrease.